The woman who ran = [videorecording (DVD)] : Domangchin yeoja - Hong, Sang-su, 1960-; Kim, Min-hŭi, 1982-; Seo Young-hwa, 1968-; Song, Seon-mi, 1976-; Kim, Sae-byŏk, 1986- (Cinema Guild, 2021)
While her husband is on a business trip, Gamhee meets three of her friends on the outskirts of Seoul. They make friendly conversation but there are different currents flowing independently of each other, both above and below the surface.